First register of Contracaecum sp. And Eustrongylides sp. (Nematoda) in kinosternon scorpioides (Linnaeus, 1766) (Testudines: Kinosternidae) from northeastern, Brazil - Lislea de Sousa, Alana (2024)
Kinosternon scorpioides (Linnaeus, 1766) popularly known in Brazil as “Jurará” is a species of chelon that serves as a food resource and source of income for some families in Northeastern Brazil. In that sense, the present study aimed to analyze the metazoan endoparasites infecting K. scorpioides from the Baixada Maranhense, Brazil. Fifteen adult specimens were captured using funnel traps in flooded fields around the Aurá River, close to the city of São Bento-Maranhão. Samples were transported to the Postgraduate Multi-User Research Laboratory- Laboratories in Postgraduate Research/Postgraduate in Animal Science located at the State University of Maranhão- UEMA for parasitological analyses. The results revealed the presence of larvae of Contracaecum sp. infecting the stomach, intestine, and liver, while Eustrongylides sp. was found encysted in the musculature, stomach, intestine, and inside an egg of a gravid female mud turtle. The findings of the present study constitute the first records of these nematodes parasitizing K. scorpioides. Since K. scorpioides is consumed as food for some families in the State of Maranhão, Brazil, and the presence of both parasites with hygienic-sanitary importance, complementary studies should be designed to allow us to understand the relationship between host parasites and whether they could have zoonotic relevance.